The heart of the school counselor: understanding passion over the span of a career - Sumerlin, Timothy Leroy, author; Littrell, John M., 1944-, advisor; Timpson, William M., advisor; Matheson, Jennifer Lynne, committee member; Carlson, Laurie A., committee member (Colorado State University. Libraries, 2009)
School counseling is a constantly evolving profession and in view of the growing demands and expectations of students, faculty, parents, the employment sector, and society in the twenty-first century, one that is in need of revision. In recent years the direction of counseling has turned to more accountability and technology, and trending away from some of the vital attributes of the heart, including passion (Palmer, 1998). Many lead counselors, staff development professionals, and administrators find themselves inadequately equipped to engage in and facilitate successful counselor professional development in these areas; school counselors’ work with students, staff, and parents suffer. The aim of this study was to demonstrate the many ways exemplary school counselors have developed and maintained passion over the span of their professional careers. Using a qualitative approach with semi-structured interviews, this study elucidated the key elements in exemplary counselors’ development of passion. Each of nine public school counselors from across Colorado schools participated in a 60 to 90 minute interview in their office and a follow-up email interview. Data analysis included constant comparative analysis with open and axial coding, which produced four emergent themes. Spirituality, humbleness, being out of the office, and a counselor’s family, each with supportive sub-themes, emerged from the interviews and are discussed. Passionate counselors exhibited deep and textured features of an ongoing spiritual life that resulted in the development of useful attributes and strategies, which in turn resulted in a variety of rewards and recognitions. These attributes, strategies, and rewards created a synergetic relationship. Personal reflections, recommendations, limitations of the study, and implications for possible future research are included.
Department Head: Timothy Gray Davies.